2017
DOI: 10.1080/17460441.2017.1349750
|View full text |Cite
|
Sign up to set email alerts
|

Novel strategies for anti-aging drug discovery

Abstract: Scientific achievements in the last few decades, leading to effective therapeutic interventions, have dramatically improved human life expectancy. Consequently, aging has become a significant problem and represents the major risk factor for most human pathologies including diabetes, cardiovascular diseases, neurological disorders, and cancer. Scientific discoveries over the past two decades have been instrumental in dissecting molecular mechanism(s) which play important roles in determining longevity. The same… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 130 publications
1
37
0
Order By: Relevance
“…With the aim of reducing off-target effects, other senolytic therapies now moving toward clinical trials are targeting cellular pathways that have greater specificity to senescent cells (Saraswat and Rizvi, 2017). When cells of our immune system (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…With the aim of reducing off-target effects, other senolytic therapies now moving toward clinical trials are targeting cellular pathways that have greater specificity to senescent cells (Saraswat and Rizvi, 2017). When cells of our immune system (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that oxidative stress, DNA damage, and inflammation play pivotal roles in age‐associated decline of physiological, genomic, metabolic, and immunological functions . Therefore, anti‐aging therapy and agents targeting these theories are developed, which have dramatically improved human life expectancy . However, based upon our current understanding, more effective and promising approaches for a successful anti‐aging strategy are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a conserved essential cellular metabolic pathway in mammalian cells (Lorincz, Mauvezin, & Juhasz, ; Mathai, Meijer, & Simonsen, ; Saraswat & Rizvi, ). Under starvation, hypoxia and oxidative stress, damaged macromolecules and organelles sequestrated in autophagosomes are degraded and recycled through delivery to lysosomes, which ensures cell survival and growth.…”
Section: Introductionmentioning
confidence: 99%